Analysis of Car Rental Information System at CV. BCD - Desti Yuvita Sari (Institute of Computer Science (IOCS), 2022)
CV. BCD is a company engaged in car rental services where this company rents out various types of cars from MPV to SUV. CV. BCD has a car rental system that runs starting from the customer who fills out a form to rent a car, then the form is submitted to the office for a rental history to be made after the verification process is complete, then the car and driver will be sent to the renter along with a receipt in the form of rental. history. Judging from the previous system that runs at the CV. BCD company in presenting the rental process that runs at the company, it is still manual, namely by using books/paper, telephone, fax, and also transportation in the submission of tenant data, making the provision of information quite long and the data is easily scattered until it is lost. . Judging from the company's business processes where there is a rental system that allows researchers to implement an online-based system, so that the rental history in the company will be properly managed, easy to access and report generation. In building this system, the researcher uses 5 stages in the system development life cycle (SDLC) method, namely planning, analysis, design, implementation, and use. Based on the analysis of system development carried out, this application can improve time efficiency, save paper costs in making rental history and facilitate data management of rental information in CV. BCD